1976
DOI: 10.1152/ajplegacy.1976.231.4.1204
|View full text |Cite
|
Sign up to set email alerts
|

Impaired urinary concentrating ability and cyclic AMP in K+-depleted rat kidney

Abstract: The possibility that an alteration of the vasopressin-dependent cyclic AMP system plays a pathogenic role in the urinary concentrating defect in K+ depletion was investigated in the rat. The antidiuretic response to vasopressin was significantly less in K+-depleted rats. In these K+-depleted rats, the increase in urinary cyclic AMP excretion in response to vasopressin was also significantly less. However, repletion of K+ for 1 wk by feeding high-K+ diets restored the ability to increase urinary cyclic AMP excr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

1978
1978
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 1 publication
(3 reference statements)
2
25
0
1
Order By: Relevance
“…Although the mechanisms by which hypokalemia causes nephrogenic diabetes insipidus are a matter of contention, it appears to be due to a reduction in the production of cAMP (the second messenger for vasopressin action) in response to vasopressin, either by direct inhibition of adenylate cyclase (2,16,25) or via increased prostaglandin production (14). Our previous observation that lithium causes a decrease in AQP2 expression could also be explained by this mechanism, as the lithium-induced polyuria is thought to be due to an inhibition of adenylate cyclase (26,27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the mechanisms by which hypokalemia causes nephrogenic diabetes insipidus are a matter of contention, it appears to be due to a reduction in the production of cAMP (the second messenger for vasopressin action) in response to vasopressin, either by direct inhibition of adenylate cyclase (2,16,25) or via increased prostaglandin production (14). Our previous observation that lithium causes a decrease in AQP2 expression could also be explained by this mechanism, as the lithium-induced polyuria is thought to be due to an inhibition of adenylate cyclase (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged hypokalemia causes substantial morphological change in kidney ultrastructure, and is associated with renal functional abnormalities, including a vasopressin-resistant decrease in urinary concentrating ability (1). The rat provides a good animal model of these effects, with changes similar to those seen in human kidney (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies using heterogenous kidney tissue preparations from KD rats showed a defect in ADH-stimulated adenylate cyclase activity and cyclic adenosine-3',5'-monophosphate (cAMP) accumulation in the medullary and papillary regions of the kidney (9,10 (12). Although these studies and ones in amphibian urinary bladders (13) indirectly suggest that an impaired hydroosmotic response to ADH exists in KD animals, the exact location along the nephron and the underlying mechanism responsible for the urinary concentrating defect remain to be shown conclusively.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in fluid delivery to late distal tubules suggests that during thiazide treatment less water is reabsorbed in the collecting ducts. This may result from a reduced sensitivity of the collecting ducts to vasopressin, possibly associated with the hypokalaemia of thiazide treatment (Beck & Webster, 1976 A paradoxical result with frusemide on sodium movements in human red blood cells BY S. C. BRAND and R. WHITTAM. Department of Physiology, The University, Leicester LEJ 7RH…”
Section: Pmentioning
confidence: 99%